THE ANALYSIS OF COMMUNITY SATISFACTION LEVEL AND PARTICIPATION IN DEVELOPMENT AT BONGO TUA VILLAGE - rokiyanto usman; Rizal; Ariyati Hamzah (Jurnal Ilmu Manajemen dan Bisnis, 2022)
This research aims ; 1) To determine community satisfaction towards development in Bongo Tua Village; 2) To find out community participation towards development in Bongo Tua Village. The research method used a qualitative approach. There were 5 informants. Descriptive analysis techniques through qualitative research through data and information obtained directly from informants then analyzed by using the existing theoretical basis and explained systematically based on facts in the field. The results showed that (1) for community satisfaction, it was considered that they did not have a form or system of suggestions and complaints, which the Bongo Tua Village Government used, because they only directly provided suggestions and complaints only through the BPD directly, there were also directly to the Bongo Tua Village Government. The form of measuring community satisfaction was by looking at the results of satisfaction surveys that were conducted periodically. It was far has been in the form of development, both physical and non-physical that supports providing community satisfaction. Even the skills and abilities in the implementation of development were considered to be lacking and there were still many people who were not enthusiastic to put attention. For public behavior in assessing the services provided by the community, it is considered not good because there were still individual attitudes in the Village Government that were not concerned with the community. (2) In terms of community participation, especially the implementation of development in Bongo Tua Village, it was considered not optimal considering that it turned out that so far participation in physical matters has been running, but participation in non-physical activities was less supportive in the implementation of development in Bongo Tua Village.